Stressors and coping strategies among single mothers during the COVID-19 pandemic. - Himawari Wakai; Nobutoshi Nawa; Yui Yamaoka; Takeo Fujiwara (PLoS ONE, 2023)
Objectives Increased levels of stress have been reported among parents due to the factors associated with the COVID-19 pandemic. Although social support is known as a protective factor for the stressors, restrictions due to the pandemic could influence the provision and forms of social support. To date, few qualitative studies have examined the stressors and coping strategies in detail. In particular, the role of social support for single mothers during the pandemic remains largely unclear. The purpose of this study is to explore the stressors and coping strategies of single parents during the COVID-19 pandemic, with a focus on social support as a coping strategy. Methods In-depth interviews with 20 single mothers were conducted in Japan between October and November 2021. Data were deductively coded using thematic coding based on codes related to stressors and coping strategies, focusing on social support as a coping strategy. Results Most interviewees recognized additional stressors after the COVID-19 outbreak. Five stressors were mentioned by the participants: (1) fear of infection, (2) financial concerns, (3) stress caused by interactions with their children, (4) restrictions on childcare facilities, and (5) stress related to staying at home. The major coping strategies were (1) informal social support from family, friends, and coworkers, (2) formal social support from municipalities or nonprofit organizations, and (3) self-coping strategies. Conclusion Single mothers in Japan recognized additional stressors after the COVID-19 outbreak. Our results support the importance of both formal and informal social support for single mothers, either in-person or online, to cope with stress during the pandemic.